Interpretation of the piezoelectric photothermal spectra of p-type silicon samples - Maliński, M.; Memon, A.; Ikari, T. (Archives of Acoustics, 2003)
This paper presents both experimental and theoretical amplitude and phase piezoelectric photothermal spectra (PPTS) of p-type silicon samples. two dominant peaks at 1.07 eV and 1.18 eV were observed in PPT spectra at room temperature. The relative intensities of these peaks change by a surface treatment. Numerical analysis is performed by supposing that an inactive layer exists at the sample surface. The characteristic structure observed in the piezoelectric amplitude spectra of p-Si samples is well explained by the model proposed for multilayer structure. We found that the proposed inactive layer model is quite helpful in investigating the surface properties of a semiconductor material.